1975
DOI: 10.3758/bf03337526
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hippocampal lesions on the development and extinction of a learned taste aversion for a novel food

Abstract: The effect of hippocampal lesions on the inhibition of eating was examined within a learned taste aversion paradigm. Rats with hippocampal lesions were tested on their ability to refrain from eating a novel tasting food that had been paired with the internal malaise produced by a .15·M IP injection of lithium chloride. The results showed that the rats with hippocampal lesions did not differ from normal rats on either the development or extinction of the aversion. These results extend previous findings which sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

1976
1976
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…These results are consistent with a number of studies (Best & Orr, 1973;Hobbs et aI., 1974;Kolb et aI., 1977;McGowan et aI., 1969;McGowan et aI., 1972;Miller et aI., 1975;Murphy & Brown, 1974;Thomka & Brown, 1975) that have shown that an intact septo-hippocampal system is not essential for taste aversion learning. In each of these earlier studies, strong conditioned taste aversions were demonstrated in rats with partial, though sometimes extensive, destruction of the hippocampus or the septum.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are consistent with a number of studies (Best & Orr, 1973;Hobbs et aI., 1974;Kolb et aI., 1977;McGowan et aI., 1969;McGowan et aI., 1972;Miller et aI., 1975;Murphy & Brown, 1974;Thomka & Brown, 1975) that have shown that an intact septo-hippocampal system is not essential for taste aversion learning. In each of these earlier studies, strong conditioned taste aversions were demonstrated in rats with partial, though sometimes extensive, destruction of the hippocampus or the septum.…”
Section: Discussionsupporting
confidence: 90%
“…Perhaps the most striking of these differences is the nature of the UCS employed. For example, four of the five studies that reported no impairment of taste aversion acquisition after large hippocampal lesions (Kolb et al, 1977;Murphy & Brown, 1974;Thomka & Brown, 1975; present study) used LiCl as the US; the fifth (Miller et al, 1975) used cyclophosphamide. On the other hand, two of the three studies reporting an acquisition deficit after hippocampal lesions (Best & Orr, 1973;Krane et al, 1976) used apomorphine as the US; the third (Miller et al, 1971) used X-ray.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…According to Thomka and Brown (1975), many of the investigations of the effects of hippocampal lesions upon the acquisition of taste aversions (Best & Orr, 1973;h0 McGowan, Hankins, & Garcia, 1972;Murphy & Brown, 1974) have relied on the use of the taste of a solution to serve as a conditioned stimulus. However, Thomka and Brown warn that the results of such studies might be misleading since some authors (Milgram, 1969;Oliver, Firestone, & Goodman, 1973) have found that the hippocampus may be involved in the control of eating but not drinking, in the rat.…”
Section: Hippocampal Lesions and Consummatory Behaviormentioning
confidence: 99%
“…However, Thomka and Brown warn that the results of such studies might be misleading since some authors (Milgram, 1969;Oliver, Firestone, & Goodman, 1973) have found that the hippocampus may be involved in the control of eating but not drinking, in the rat. Thomka and Brown (1975) studied the role of the hippocampus in the control of cating, by utilizing the learned taste aversion procedure. Some rats received hippocampal or cortical ablations, while a third group served as unoperated controls.…”
Section: Hippocampal Lesions and Consummatory Behaviormentioning
confidence: 99%